Islamic capital markets : a comparative approach - Ismath Bacha, Obiyathulla; Mirakhor, Abbas (Singapore : Wiley, 2013)
A comprehensive examination of Islamic capital markets Taking a comparative approach to the subject, this text looks at the similarities and differences between Islamic capital markets and conventional capital markets. The book explains each particular topic from both the conventional and the Islamic perspective, offering a full understanding of Islamic capital markets, processes, and instruments. In addition to a full explanation of Islamic products, this approach also ensures a holistic understanding of the dual markets within which Islamic capital markets operate. Ideal for b.
Chapter 3: Islamic Finance: Underlying Philosophy, Contracts, Instrument Design, and RequisitesIntroduction and Overview; Chapter Topics; Chapter Objective; Key Terms; 3.1: Introduction; 3.2: Underlying Themes and Fundamentals of Fiqh Mu'amalah; 3.3: Requirements for Islamic Capital Market Instruments/Transactions; 3.3.1: Riba; 3.3.2: Gharar; 3.3.3: Maisyir; 3.3.4: Jahl; 3.4: Shariah-Based Contracts for Financial Transactions; 3.4.1: Other Commonly Used Capital Market Contracts; 3.5: International Regulatory Institutions for Islamic Finance.
Includes bibliographical references and index.
Print version record.
Keywords: Banks and banking -- Islamic countries; Capital market -- Islamic countries; Finance -- Islamic countries; Banks and banking -- Islamic countries; Business; Capital market -- Islamic countries; Finance -- Islamic countries; Electronic books